The dasein of peasant girls during the violence in Colombia (2019)
The text explores the experience lived during the period known as The Violence in Colombia by women now over 80. It examines the “trauma” that, according to the author, manifests itself in the form of “scratches”, thus making it difficult to translate and interpret given that it is only perceptible through listening. The article discusses M. Heidegger's notions of Dasein and being-in-the-world, that is, our thrownness into the world in a specific context in which we construct our subjectivity and learn how to live, in order to understand them through these singular feminine experiences. © 2019 Universidad Nacional de Colombia. All rights reserved.